Emergency physician stressors, concerns, and behavioral changes during COVID‐19: A longitudinal study. (16th February 2021) - Baumann, Brigitte M.; Cooper, Richelle J.; Medak, Anthony J.; Lim, Stephen; Chinnock, Brian; Frazier, Remi; Roberts, Brian W.; Epel, Elissa S.; Rodriguez, Robert M.
Abstract: Objectives: The objective was to provide a longitudinal assessment of anxiety levels and work and home concerns of U.S. emergency physicians during the COVID‐19 pandemic. Methods: We performed a longitudinal, cross‐sectional email survey of clinically active emergency physicians (attending, fellow, and resident) at seven academic emergency departments. Follow‐up surveys were sent 4 to 6 weeks after the initial survey and assessed the following: COVID‐19 patient exposure, availability of COVID‐19 testing, levels of home and workplace anxiety/stress, changes in behaviors, and performance on a primary care posttraumatic stress disorder screen (PC‐PTSD‐5). Logistic regression explored factors associated with a high PC‐PTSD‐5 scale score (≥3), indicating increased risk for PTSD. Results: Of the 426 surveyed initial respondents, 262 (61.5%) completed the follow‐up survey. While 97.3% (255/262) reported treating suspected COVID‐19 patients, most physicians (162/262, 61.8%) had not received testing themselves. In follow‐up, respondents were most concerned about the relaxing of social distancing leading to a second wave (median score = 6, IQR = 4–7). Physicians reported a consistently high ability to order COVID‐19 tests for patients (median score = 6, IQR = 5–7) and access to personal protective equipment (median score = 6, IQR = 5–6). Women physicians were more likely to score ≥ 3 than men on the PC‐PTSD‐5 screener on the initial survey (43.3% vs. 22.5%; Δ 20.8%, 95% confidence interval [CI] = 9.3% to 31.5%), and despite decreases in overall proportions, this discrepancy remained in follow‐up (34.7% vs. 16.8%; Δ 17.9%, 95% CI = 7.1% to 28.1%). In examining the relationship between demographics, living situations, and institution location on having a PC‐PTSD‐5 score ≥ 3, only female sex was associated with a PC‐PTSD‐5 score ≥ 3 (adjusted odds ratio = 2.48, 95% CI = 1.28 to 4.79). Conclusions: While exposure to suspected COVID‐19 patients was nearly universal, stress levels in emergency physicians decreased with time. At both initial and follow‐up assessments, women were more likely to test positive on the PC‐PTSD‐5 screener compared to men.